Histological Examination of the Effects of Agomelatine in an Experimental Abortion Model - Pervin, Mehtap; Sayin, Orhan; Bozyil, Ahmed Sait; Ozdede, Mehmet Ridvan; Batmaz, Husna; Yasar, Busenur; Kacar, Emine (Wiley, 2025)
[Abstract Not Available]
Keywords: Abortion; Agomelatine; Histology; Pregnancy; Rat